Influenza: Can we cope better with the unpredictable? - Dos Santos, Gaël (Hum Vaccin Immunother, 2015)
Seasonal influenza vaccines are unique because they are regularly reformulated and prepared in anticipation of the upcoming influenza season. Selection of vaccine strains occurs in advance of the influenza season, allowing time for vaccine production. Influenza viruses constantly evolve, and mismatches between vaccine strains and circulating strains have occurred in the past, impacting on vaccine effectiveness. The public health impact of a mismatch depends on multiple factors including strain virulence and transmission dynamics, pre-existing population immunity to the drift strain, and cross-reactivity induced by vaccination. Influenza vaccine effectiveness thus varies unpredictably from year to year, and may differ across European and northern American regions. Here we highlight the unpredictability associated with influenza virus circulation and present a comprehensive picture of circulating influenza strains in the northern hemisphere as compared to WHO recommendations for vaccine strains over the last 15 y. In years when vaccine mismatch occurs, such as the 2014–15 influenza season, public health agencies continue to recommend influenza vaccination as the preferred means by which to protect against influenza and influenza-associated complications. Research is on-going to optimise strain selection and vaccine composition to improve effectiveness.